Taxonomic revision of the land snail genera Macrochlamys Gray, 1847 and Sarika Godwin-Austen, 1907 (Eupulmonata: Ariophantidae) from south-eastern Myanmar, with descriptions of three new species. (2nd April 2020) - Pholyotha, Arthit; Sutcharit, Chirasak; Tongkerd, Piyoros; Lin, Aung; Panha, Somsak
ABSTRACT: Knowledge of Myanmar land snails is based on the late eighteenth to early twentieth century literature and many species need to be re-investigated, especially in the genera Macrochlamys Gray, 1847 and Sarika Godwin-Austen, 1907. In order to update this knowledge, this paper presents information on these two related genera based on new materials from south-eastern Myanmar. Fifteen species are recognised in the south-east of Myanmar. Of these, live material was available for eight Macrochlamys and Sarika species and these are described in full herein, based on data from the shell, external morphology and genitalia, including three species new to science ( M. brachystia n. sp., S. concavata n. sp. and S. lopa n. sp.) and five species redescribed ( M. aspides, M. kelantanensis, M. petasus, S. consepta and S. obesior ). The remaining five species are known only from their shell morphology ( M. cauisa, M. perpaula, M. poongee, M. salwinensis and S. birmana ) and two species are known from genitalia ( S. dugasti and S. resplendens ). For these species the shells are figured and some taxonomic remarks are provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:58D2A9E7-50FD-49C2-B2F4-4D00457EA331